Development of an Inquiry-Based Science Learning Material Using Flash Card to Reduce Misconception of Elementary School Students - Intan Ika Ashhabul Maimanah; Suryanti; Nadi Suprapto (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2020)
This study is development research with the aim the knowing of validity, effectiveness, and practicality of inquiry-based learning tools assisted by flashcard media to reduce misconceptions of elementary school students on light concept. Before and after the learning materials implemented, the pretest and posttest were carried out. Identification of students' misconceptions was utilized by using the three-tiers diagnostic test. The data analysis technique used quantitative descriptive. The results of the study showed: (1) The validity of the learning materials was declared to be very valid by the validator, (2) The practicality of the materials developed was declared practical by the observer in terms of aspects of the device's implementation and student activities in learning which were categorized very well, and (3) the effectiveness of the learning materials being developed was declared effective in terms of the application of the materials which had an impact on reducing students' misconceptions which initially amounted to 57.33% down to 17.33%. An Inquiry-based science learning device assisted with flashcard media that has been developed, was feasible with valid, practical, and effective criteria, and also can be used to reduce science misconceptions on elementary students on light material.